Fabrication and performance analysis of titania-polyurea spray coating in marine application - Li, Yuanzhe (Nanyang Technological University, 2021)
Marine structures often suffer from biofouling, which greatly increase the resistance of the ship’s hull and turbine blades. Extensive biofouling can even lead to the failure of the coating structures. From the current trend of antibacterial materials development, the use of hydrophobic texture combined with antibacterial agents is a promising antibacterial means. Besides, Polyurea coatings with extreme physicochemical properties also provide a great solution as well as a platform for the fabrication of new type coatings. However, a study on application of Titania-Polyurea spray coating for marine use against biological fouling as well as abrasion impact is still lacking.